In vitro antifungal and antioxidant activities of two Benin medicinal plants - LAGNIKA, LATIFOU (My University, 2014)
Casuarina equisetifolia (L.) (Casuarinaceae) and Oxalis corniculata (L.) (Oxalidaceae), two medicinal plants used in Bénin were screened for their antifungal activity against six strains of the genus Aspergillus (Aspergillus fumigatus, Aspergillus flavus, Aspergillus terreus, Aspergillus parasiticus, Aspergillus ochraceus and Aspergillus nidulans). The antioxidant activity and phytochemical constituents were also examined. The extracts were screened for the presence of alkaloids, coumarin, anthracene derivatives, flavonoids, lignans, essential oils, naphtoquinones and terpenoids. The antifungal activity was carried out using agar diffusion method, while antioxidant activity was determined by the 2,2-diphenylpicrylhydrazine method. Phytochemical investigation revealed the presence of flavonoids, anthracenic derivatives, essential oil, pigments, terpene and triterpene in the leaves of O. corniculata and terpene and pigments in the fruits of C. equisetifolia. The antifungal activity of extracts is more marked on the sporulation (17.74 to 99.48%) than the mycelia development (7.69 to 65.71%). Methanol and hydro-ethanol extracts showed the best inhibitory percentage of DPPH radical (78 to 95%).
Keywords: Medicinal plants; antifungal and antioxidant activity; phytochemical.